INTEGRASI NILAI-NILAI KEMANUSIAAN UNIVERSAL DALAM PENDIDIKAN PANCASILA: PERSPEKTIF FILSAFAT HINDU - Darsana, I Made; Gayatri, Kamisriati Levi (Widya Katambung, 2024)
Universal human values serve as the cornerstone for building national character and realizing a just, peaceful, and prosperous society. Amidst the turmoil of globalization and modernization, instilling universal human values from an early age becomes crucial. Pancasila Education as a crucial subject in schools plays a strategic role in inculcating these values. Hindu philosophy, with its rich trove of universal human values, offers immense potential for integration into Pancasila Education. This journal aims to explore the universal human values embedded in Hindu philosophy and how these values can be integrated into Pancasila Education. Integrating Hindu philosophical values into Pancasila Education holds numerous benefits for Indonesia's younger generation. These values can help them develop into individuals with strong morals, noble character, and a deep respect for universal human values. While challenges and obstacles exist, this integration can yield immense benefits for Indonesia's youth and the nation's future.